2012
DOI: 10.1016/j.chembiol.2012.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Correction of F508del-CFTR Trafficking by the Sponge Alkaloid Latonduine Is Modulated by Interaction with PARP

Abstract: Mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene cause CF. The most common mutation, F508 deletion, causes CFTR misfolding and endoplasmic reticulum retention, preventing it from trafficking to the cell surface. One approach to CF treatment is to identify compounds that correct the trafficking defect. We screened a marine extract collection and, after extract, deconvolution identified the latonduines as F508del-CFTR trafficking correctors that give functional correction in vivo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 39 publications
2
43
0
Order By: Relevance
“…bisacetylenic alcohol ( 191 ) [184]; conicasterol E ( 192 ) [185]; 6”-debromohamacanthin A ( 193 ) [186]; dieckol ( 194 ) [187]; fructigenine A ( 195 ) [188]; geoditin A ( 196 ) [189]; gorgosterol ( 197 ) [190]; gracilioether B ( 198 ) [191]; gracilioether K ( 199 ) [192]; herdmanine K ( 200 ) [193]; hyrtioreticulin A ( 201 ) [194]; new Kunitz-type protease inhibitor InHVJ ( 202 ) [195]; jaspamide ( 203 ) [196]; latonduine A ( 204 ) [197]; leucettine L41 ( 205 ) [169]; manzamine A ( 206 ) [198]; nahuoic acid A ( 207 ) [199]; namalide ( 208 ) [200]; ningalins C and D ( 209 , 210 ) [201]; octaphlorethol A ( 114 ) [120]; petrosaspongiolide M ( 211 ) [202]; petrosiol A ( 212 ) [203]; phidianidine A ( 213 ) [204]; Poly-APS ( 214 ) [205]; Pseudoceratina sp. dibromotyrosine ( 215 ) [206]; pseudopterosin A ( 216 ) [207]; sargachromanol G ( 217 ) [208]; S. graminifolium polysaccharide ( 218 ) [209]; S. patens phloroglucinol ( 219 ) [210]; S. xiamenensis benzopyran ( 220 ) [211]; theonellasterol ( 221 ) [212]; toluquinol ( 222 ) [213]; and U. lactuca fatty acid ( 223 ) [214].…”
Section: Marine Compounds With Miscellaneous Mechanisms Of Actionmentioning
confidence: 99%
“…bisacetylenic alcohol ( 191 ) [184]; conicasterol E ( 192 ) [185]; 6”-debromohamacanthin A ( 193 ) [186]; dieckol ( 194 ) [187]; fructigenine A ( 195 ) [188]; geoditin A ( 196 ) [189]; gorgosterol ( 197 ) [190]; gracilioether B ( 198 ) [191]; gracilioether K ( 199 ) [192]; herdmanine K ( 200 ) [193]; hyrtioreticulin A ( 201 ) [194]; new Kunitz-type protease inhibitor InHVJ ( 202 ) [195]; jaspamide ( 203 ) [196]; latonduine A ( 204 ) [197]; leucettine L41 ( 205 ) [169]; manzamine A ( 206 ) [198]; nahuoic acid A ( 207 ) [199]; namalide ( 208 ) [200]; ningalins C and D ( 209 , 210 ) [201]; octaphlorethol A ( 114 ) [120]; petrosaspongiolide M ( 211 ) [202]; petrosiol A ( 212 ) [203]; phidianidine A ( 213 ) [204]; Poly-APS ( 214 ) [205]; Pseudoceratina sp. dibromotyrosine ( 215 ) [206]; pseudopterosin A ( 216 ) [207]; sargachromanol G ( 217 ) [208]; S. graminifolium polysaccharide ( 218 ) [209]; S. patens phloroglucinol ( 219 ) [210]; S. xiamenensis benzopyran ( 220 ) [211]; theonellasterol ( 221 ) [212]; toluquinol ( 222 ) [213]; and U. lactuca fatty acid ( 223 ) [214].…”
Section: Marine Compounds With Miscellaneous Mechanisms Of Actionmentioning
confidence: 99%
“…This approach has recently shown great promise. Screening efforts have yielded a number of compounds that may offer general therapeutic utility for misfolding diseases (Calamini et al, 2012; Carlile et al, 2012; Mu et al, 2008; Tardiff et al, 2013). Interestingly, the rescue afforded by PRs seems to arise through diverse biochemical mechanisms including the modulation of ER stress pathways (Ozcan et al, 2006; Ryno et al, 2013; Wiseman & Balch, 2005), the tuning of heat shock protein (HSP) expression and activity (Calamini et al, 2012), inhibition of the proteasome (Mu et al, 2008), and inhibition of ubiquitin ligases (Tardiff et al, 2013).…”
Section: Proteostasis and The Cellular Trafficking Of α-Helical Mementioning
confidence: 99%
“…Using chemical proteomics, several PARPs, i.e., PARPs 1-4, as well as TNKS1 and 2, were identified as latonduine binders. Functional analysis revealed that in particular PARP-3 activity is inhibited by latonduines [235]. In accordance with this, another study revealed that inhibiting PARPs, and in particular PARP1, activities restores F508del-CFTR trafficking in different cell lines and mouse embryonic fibroblasts [236].…”
Section: A Role For Parylation In Protein Folding and The Unfolded Prmentioning
confidence: 69%